Review of the genus Superciliaris Meng, Qin & Wang, 2020 (Hemiptera, Fulgoroidea, Issidae): from island endemic to wide Oriental distribution - Gnezdilov, Vladimir M. (European Journal of Taxonomy, 2022)
Three new species of the genus Superciliaris Meng, Qin & Wang, 2020 are described from southern Vietnam, Malaysia (northern Borneo), and Indonesia (northern Sulawesi). The genus is recorded for the first time from mainland Asia and Sunda Archipelago. A key to species of Superciliaris is given. The relationships of the species are discussed.